To The Problem of Spirituality - Seytmuratov Nurlanbek (Zien Journals, 2021)
This article provides a philosophical analysis of spirituality and evaluates it. We have tried to shed light on the factors influencing the spirituality of the independence period
Keywords: Spirituality; religion; politics; development